2019
DOI: 10.14704/nq.2019.17.7.2562
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiology of Chronic Stress: An Example of Mind-body Interaction

Abstract: We present an example of mind-body interaction through the psychophysiology of chronic stress. We show the dynamic pattern of effects on the mind and body associated with chronic stress response and recognize how the mind coordinates the body systems to sustain internal equilibrium for optimal function. In fact many other bodily illnesses are caused by an interaction of mental and physical subtleties. It is important to note that these psychophysiological disorders bring actual physical damage. This review pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
0
16
0
3
Order By: Relevance
“…This concept is characterized by exhaustion (energy depletion), negativism, and reduced professional efficacy. Moreover, stress was defined in the literature as the feeling of being overwhelmed or unable to cope with internal and external stressors, and it involves physiological or psychological changes and responses [ 15 ]. Therefore, it would affect the individual’s health.…”
Section: Introductionmentioning
confidence: 99%
“…This concept is characterized by exhaustion (energy depletion), negativism, and reduced professional efficacy. Moreover, stress was defined in the literature as the feeling of being overwhelmed or unable to cope with internal and external stressors, and it involves physiological or psychological changes and responses [ 15 ]. Therefore, it would affect the individual’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Mood and physical condition are closely related, and evidence of the impact of depression and other mood states on numerous physical illnesses is increasing [ 30 ]. Stress stimulation triggers and exacerbates the dysregulation of HPA function, which leads to the physical, cognitive, emotional, and behavioral symptoms of depressive disorder [ 1 ]. HPA changes are also associated with peripheral disorders such as metabolic and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mind–body interaction, or the concept that the mind and body are connected, is useful for understanding psychophysiology in the field of mental health [ 1 ]. For instance, strong evidence has accumulated about the link between hypothalamic–pituitary–adrenal (HPA) axis dysregulation and the risk of developing mental illness [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“… 17 It is suggested that patients with mental health disorders diagnosed with a health condition may have lifestyle adjustment difficulties causing significant stress which can produce symptoms of malaise, irritability, and fatigue. 17 , 18 , 19 These symptoms may have a significant impact on the QoL ultimately resulting in life dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%